Analisis Penurunan Tanah Timbunan Menggunakan Metode Elemen Hingga pada Ruas Jalan Tolango-Bulontio STA 47+600 - I.P. Latief; I.M. Patuti; F. Achmad (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2023)
Subsidence is a change in the composition of the soil and small spaces in the soil. The method that can be chosen to reduce the rate of decline that occurs on the road is preloading and adding geotextiles. The purpose of this study was to analyze the settlement that occurred in the embankment soil before and after the geotextile was applied. The research location is on Jalan Tolango-Bulontio STA. 47+600 Wubudu Village, East Sumalata District, North Gorontalo Regency. The primary data used is the characteristics of the embankment soil, while the secondary data is in the form of plan drawings, N-SPT values, and geotextile characteristics. Land subsidence analysis was carried out by modeling in two dimensions using the finite element method with the help of the Plaxis 2d v20 application. Structural modeling using plane strain model. The results showed that the settlement of the embankment using geotextiles that the settlement of the embankment soil at point A (shoulder) was 33 mm <65 mm, while the settlement of the embankment without geotextile was greatest at point A (shoulder) of 33 mm. mm < 65 m (allowable descent). The settlement value of the embankment without geotextiles and the use of geotextiles did not have a significant difference because the geotextiles used only functioned as filtration, not as reinforcement